KELELAHAN KERJA (WORK FATIGUE) - Ryna Parlyna; Arif Marsal (Fakultas Ekonomi Universitas Negeri Jakarta, 2013)
Abstract Numbers of definition has long been defined by the schoolers, but in a simple terms fatigue is a systom of being tired. Fatigue is a common feeling felt by the working population. Increasing pressure to become more competitive in the industry elsewhere rised the number of working people to work longer hours with a significant workload, which eventually lead to a number of employees becoming fatigue. Keyword : Work Fatigue, Causal factors of Work Fatigue, Health and Safety